MULTIDISCIPILINARY APPROACH FOR MANAGEMENT OF ENDODONTICALLY TREATED MUTILATED TOOTH –CASE REPORT - Pardeep, Singh; Kirtika, Sheoran; Aditi, Singh; Gyanander, Attresh; Sandeep, Manchanda (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
A grossly decayed tooth sometime poses difficulty in fabrication of FPD, The post core is often required to gain support from the remaining tooth structure. This case report describes a simple and scientific multidisciplinary approach towards management of endodontically treated mutilated tooth. Proper analysis and treatment planning is required for correction of esthetic and functional demand of mutilated tooth.